Enthusiastic claimants, reluctant courts: The empirical and critical analysis of punitive damages in Chinese intellectual property law - Baiyang Xiao (The Journal of World Intellectual Property, 2024)
The availability of punitive awards varies across different common law jurisdictions. In recent years, China, as a civil law jurisdiction, has progressively introduced a comprehensive punitive damages system in Intellectual Property (IP) law in recent years. To investigate how this common law product functions in the civil law system, this paper scrutinizes the evolution and functions of punitive damages and depicts the map of punitive damages in Chinese IP law. Then this paper reports and analyses 657 IP judgments involving the application of punitive damages that were tried and decided in all parts of mainland China by all levels of courts from June 1, 2021, to May 31, 2022. Our empirical data shows that punitive damages are frequently sought by claimants, yet courts are reluctant to award them due to the complexities in determining the basis for calculation and judges' reluctance towards detailed legal reasoning. Furthermore, a critical analysis of the application of punitive damages in IP trials is provided, critiquing the court's preference for statutory damages, the complexity in determining the basis and multipliers for calculation, and the strict standard of proof, which accounted for the small portion of punitive damages awarded in judicial practices.
Keywords: 340; Chinese intellectual property law; empirical legal study; punitive damages